(untitled) (Research, Society and Development, 2020)
Leprosy is an infectious disease that manifests itself mainly through dermatoneurological signs and symptoms. This study analyzed the knowledge and practices of higher education professionals from the Family Health (eSF) team about the interrelationship between leprosy and its oral alterations. This is a cross-sectional, observational and analytical study, with a quantitative approach. The convenience sample comprised 24 doctors, 45 nurses and 24 dentists (CDs) from the eSF of a municipality in the Northeast of Brazil. The data collection instrument was a structured questionnaire with 5-point Likert scales. Based on the research scores, it was interpreted that the professionals have "insufficient" knowledge about oral alterations in leprosy and an "adequate" practice. Evidence signaled the need to improve knowledge about oral alterations in leprosy and the organization of professional practices of all those involved in eSF, because to ensure comprehensive care it is essential to awaken to the importance of dental practices in the development of leprosy control actions in the eSF.